Crosslinked polythiophene compound, sulfur-carbon composite material, lithium-sulfur battery and method for manufacturing sulfur-carbon composite material
By using crosslinked polythiophene compounds and sulfur-carbon composites in lithium-sulfur batteries to capture lithium polysulfide, the problem of shortening of lithium-sulfur battery life is solved, and the battery capacity is maintained and the life is extended.
Patent Information
- Application Number
- CN202380041360.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-20
- Filing Date
- 2023-09-19
- Publication Date
- 2024-12-17
AI Technical Summary
Lithium polysulfide leaking from the positive electrode in lithium-sulfur batteries causes the battery life to be shortened, and the existing technology has failed to effectively solve this problem.
Using crosslinked polythiophene compounds and sulfur carbon composite materials, a sulfur carbon composite material with cationic functional groups is formed by coating the crosslinked polythiophene compounds on the porous carbon material and supporting the sulfur compound. It is used to capture lithium polysulfide and prevent its migration. to the negative pole.
It effectively inhibits the migration of lithium polysulfide, maintains the charging and discharge capacity of lithium sulfur batteries, and extends the battery life.
Smart Images

Figure CN119156410A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cross-linked polythiophene compound capable of capturing polysulfide leaked from a positive electrode to improve battery life and a battery comprising the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0118937 filed in Korea on September 20, 2022, the disclosure of which is incorporated herein by reference. Background Art
[0003] With the technological development and growing demand for mobile devices, there is an increasing demand for secondary batteries as an energy source, and among secondary batteries, lithium secondary batteries have been marketed and widely used due to their high energy density, high operating potential, long cycle life and low self-discharge rate.
[0004] In recent years, as people pay more and more attention to environmental issues, many studies have been conducted on electric vehicles (EV) and hybrid electric vehicles (HEV), which are alternatives to vehicles using fossil fuels such as gasoline vehicles and diesel vehicles, which are considered to be one of the main causes of air pollution. Lithium secondary batteries with high energy density, high discharge voltage and stable output have been mainly studied and used as power sources for electric vehicles and hybrid electric vehicles.
[0005] The lithium secondary battery has a structure in which an electrode assembly includes a positive electrode and a negative electrode, each electrode includes an electrode collector and an active material coated on the electrode collector, wherein a porous separator is interposed between the positive electrode and the negative electrode, and a nonaqueous electrolyte including a lithium salt is wetted to the electrode assembly.
[0006] At present, the lithium secondary battery market is controlled by the technology of lithium cobalt oxide LiCoO2 at the positive electrode based on pairing and graphite at the negative electrode. The rated voltage of lithium secondary batteries is about 3.6 V, while the rated voltage of most other types of batteries (Ni-Cd, Ni-MH, etc.) is 1.5 V. The energy density per unit volume and the energy density per unit mass are respectively about 300 to 500Wh / l and 160 to 200 Wh / kg. This value is the highest value among all batteries currently on the market. In addition, this type of battery has low self-discharge and long life (500 or 1000 cycles). Despite the surprising performance achievements, the performance difference between all lithium ion batteries is not great at present, and it is foreseen that improvements will only be carried out in a very limited range.
[0007] Therefore, lithium-sulfur (Li-S) batteries are emerging as an alternative to known lithium-ion batteries.
[0008] In the same way as lithium-ion secondary batteries, lithium-sulfur batteries work by moving lithium ions in an electrolyte between the positive electrode and the negative electrode. However, in contrast to lithium-ion secondary batteries, which aim to store energy by reactions in which lithium ions are embedded in the molecules of the electrode active material, lithium-sulfur batteries work based on oxidation and reduction reactions between sulfur and lithium ions because they use only sulfur, causing changes in the electrode structure. Therefore, compared to lithium-ion secondary batteries, lithium-sulfur batteries can theoretically have a higher capacity at the same volume without restrictions on the electrode structure. Due to this feature, in a lithium-sulfur battery comprising a sulfur positive electrode and a lithium metal negative electrode, when it is assumed that elemental sulfur (S8) with a ring structure is completely reduced to lithium sulfide (Li2S), the theoretical capacity is 1,675 mAh / g and the theoretical energy density is 2,600 Wh / kg, which are 3 to 6 times higher than other existing battery systems (Ni / MH battery: 450 Wh / kg, Li / FeS: 480 Wh / kg, Li / MnO2: 1,000 Wh / kg, Na / S: 800 Wh / kg).
[0009] On the other hand, existing transition metal oxide-based lithium-ion secondary batteries can be considered as batteries containing materials that are sources of heavy metal pollution, because they contain oxides of nickel (Ni), cobalt (Co), and manganese (Mn) in the positive electrode with a density higher than that of heavy metals (metals above 5 g / mL). However, lithium-sulfur batteries do not contain materials that cause pollution and contain non-toxic materials, so they are considered environmentally friendly in this respect. In addition, sulfur, a positive electrode material, is abundant and inexpensive on Earth.
[0010] On the other hand, in lithium-sulfur batteries, sulfur undergoes a reduction reaction and lithium metal undergoes an oxidation reaction during discharge, and in this case, sulfur forms linear-structured lithium polysulfide (LiPS) from a ring-structured S8, and the lithium-sulfur battery shows a step-type discharge voltage until the lithium polysulfide is completely reduced to Li2S. However, while the lithium-sulfur battery is charged and discharged, the charge and discharge efficiency decreases and the battery life is shortened. As described above, the shortened life of the lithium-sulfur battery is caused by many different factors such as side reactions of the electrolyte, instability of lithium metal, and accumulation of positive electrode byproducts (e.g., lithium polysulfide dissolution from the positive electrode).
[0011] That is, in a lithium-sulfur battery using a sulfur compound as a positive electrode active material and an alkali metal such as lithium as a negative electrode active material, lithium polysulfide is dissolved during charging and discharging, and the lithium polysulfide leaked from the positive electrode migrates to the negative electrode, which reduces the capacity of the lithium-sulfur battery and shortens the life of the lithium-sulfur battery. That is, because the lithium polysulfide leaked from the positive electrode has a high solubility in the electrolyte, the lithium polysulfide may inadvertently migrate to the negative electrode through the electrolyte through the separator, causing irreversible loss of the positive electrode active material, thereby causing capacity decay, and sulfur particles accumulate on the surface of the lithium metal due to side reactions, resulting in a shortened battery life.
[0012] In order to solve the problem of shortened life caused by lithium polysulfide, research has been conducted in the art to add reaction mitigation materials to the negative electrode to prevent side reactions from occurring on the surface of lithium metal, but no significant results have been achieved. Summary of the invention
[0013] Technical issues
[0014] One embodiment of the present invention is directed to providing a cross-linked polythiophene compound capable of capturing lithium polysulfide leaked from a positive electrode to improve the lifespan of a lithium-sulfur battery.
[0015] Another embodiment of the present invention is to provide a sulfur-carbon composite material capable of capturing lithium polysulfide leaked from a positive electrode to improve the life of a lithium-sulfur battery.
[0016] Another embodiment of the present invention is directed to a lithium-sulfur battery comprising a sulfur-carbon composite material.
[0017] Another embodiment of the present invention is directed to a method for manufacturing a sulfur-carbon composite material.
[0018] Technical Solution
[0019] In order to solve the above-mentioned problems of the present invention, a cross-linked polythiophene compound, a sulfur-carbon composite material, a lithium-sulfur battery, and a method of manufacturing the sulfur-carbon composite material according to the following embodiments are provided.
[0020] According to a first embodiment, there is provided a cross-linked polythiophene compound having a cross-linked structure and including a cationic functional group.
[0021] According to a second embodiment, in the first embodiment, the cationic functional group may include at least one of a nitrogen cation, an oxygen cation, or a sulfur cation.
[0022] According to a third embodiment, in the second embodiment, the cationic functional group may be a quaternary ammonium functional group.
[0023] According to a fourth embodiment, in the third embodiment, the crosslinked polythiophene compound may include a dialkylamine group having a quaternary ammonium functional group.
[0024] According to a fifth embodiment, in the first embodiment, the crosslinked polythiophene compound may further include a halogen anion as a counter ion of a cation included in the cationic functional group.
[0025] According to the sixth embodiment, in the first embodiment, the cross-linked polythiophene compound may be represented by Chemical Formula 1 as follows.
[0026] [Chemical formula 1]
[0027]
[0028] Wherein in Chemical Formula 1,
[0029] R 1 , R 3 , R 5 , R 7 and R 9 are each independently a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms,
[0030] R 2 and R 6 are each independently a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 20 carbon atoms, or a -COO- group,
[0031] R 4 and R 8 is a divalent cation linking group,
[0032] A is F, Cl, Br or I, and
[0033] n and m are each independently 1 to 1,000,000.
[0034] According to the seventh embodiment, in the sixth embodiment, the divalent cation linking group may be -NR 10 R 11 , and R 10 and R 11 Each may independently be hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0035] According to the eighth embodiment, in the sixth embodiment, the cross-linked polythiophene compound may be represented by Chemical Formula 2 as follows.
[0036] [Chemical formula 2]
[0037]
[0038] In Chemical Formula 2, n and m are each independently 1 to 1,000,000.
[0039] According to a ninth embodiment, there is provided a sulfur-carbon composite material, the sulfur-carbon composite material comprising:
[0040] Porous carbon materials;
[0041] a coating layer provided on at least one surface of the porous carbon material and comprising the cross-linked polythiophene compound according to any one of the first to eighth embodiments; and
[0042] A sulfur compound present in at least a portion of the surface of the porous carbon material or the inside of the pores of the porous carbon material or the surface of the coating layer.
[0043] According to the tenth embodiment, in the ninth embodiment, a weight ratio of the porous carbon material to the cross-linked polythiophene compound may be 99:1 to 85:15.
[0044] According to an eleventh embodiment, in the ninth embodiment, a weight ratio of the porous carbon material having a coating layer to the sulfur compound may be 3:7 to 4:6.
[0045] According to a twelfth embodiment, a lithium-sulfur battery is provided, wherein the lithium-sulfur battery comprises:
[0046] Positive electrode, negative electrode and separator between the positive electrode and the negative electrode,
[0047] wherein the positive electrode comprises the sulfur-carbon composite material according to any one of the ninth to eleventh embodiments.
[0048] According to a thirteenth embodiment, there is provided a method for manufacturing the sulfur-carbon composite material according to any one of the ninth to eleventh embodiments, the method comprising the steps of:
[0049] introducing a polythiophene compound into a dispersion of a porous carbon material to coat the polythiophene compound on at least one surface of the porous carbon material;
[0050] cross-linking the polythiophene compound coated on the porous carbon material to form a cross-linked polythiophene compound; and
[0051] The sulfur compound is loaded into the porous carbon material coated with the cross-linked polythiophene compound.
[0052] According to the fourteenth embodiment, in the thirteenth embodiment, the cross-linked polythiophene compound may be formed by adding a cross-linking agent to the porous carbon material coated with the polythiophene compound and performing a heat treatment.
[0053] According to a fifteenth embodiment, in the fourteenth embodiment, the cross-linking agent may comprise a dihaloalkane compound.
[0054] According to the sixteenth embodiment, in the thirteenth embodiment, the polythiophene compound may be represented by Chemical Formula 3 as follows.
[0055] [Chemical formula 3]
[0056]
[0057] Wherein in chemical formula 3,
[0058] R 1 and R 3 are each independently a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms,
[0059] R 2 is a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 20 carbon atoms, or a -COO- group,
[0060] R 12 For-NR 10 R 11 , R 10 and R 11 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and
[0061] n is 1 to 1,000,000.
[0062] According to the seventeenth embodiment, in the sixteenth embodiment, the method for preparing a polythiophene compound may include the following steps:
[0063] manufacturing a thiophene monomer having a thiophene group and a cationic functional group;
[0064] introducing a thiophene monomer into a dispersion of a porous carbon material; and
[0065] The thiophene monomers are polymerized.
[0066] According to the eighteenth embodiment, in the seventeenth embodiment, the thiophene monomer may be in situ polymerized on the surface of the porous carbon material.
[0067] According to the nineteenth embodiment, in the seventeenth embodiment, the preparation of the thiophene monomer may include the following steps:
[0068] preparing a thiophene compound having an anionic functional group;
[0069] reacting a thiophene compound with a chloride; and
[0070] The thiophene compound subjected to the reaction with the chloride is reacted with an alcohol compound having a cationic functional group to produce a thiophene monomer.
[0071] According to a twentieth embodiment, there is provided a method for manufacturing the sulfur-carbon composite material according to any one of the ninth to eleventh embodiments, the method comprising the steps of:
[0072] cross-linking the polythiophene compound to form a cross-linked polythiophene compound;
[0073] loading a sulfur compound into a porous carbon material; and
[0074] The cross-linked polythiophene compound is coated on at least one surface of the porous carbon material supported with the sulfur compound.
[0075] Beneficial Effects
[0076] The sulfur-carbon composite material of the present invention comprises a cross-linked polythiophene compound, and the cross-linked polythiophene compound has a cationic functional group. Since the cross-linked polythiophene compound having a cationic functional group is coated on the sulfur-carbon composite material, the dissolution of lithium polysulfide from the positive electrode of the lithium-sulfur battery can be suppressed by the cationic functional group, and the volume expansion of the positive electrode during the battery charge and discharge can be alleviated by the cross-linked structure of the cross-linked polythiophene compound. Therefore, sulfur particles can be prevented from accumulating on the lithium metal surface of the negative electrode, thereby maintaining the charge and discharge capacity of the lithium-sulfur battery and improving the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] The accompanying drawings show exemplary embodiments of the present invention and, together with the following detailed description, are used to provide a further understanding of the technical aspects of the present invention, and thus the present invention should not be construed as being limited to the accompanying drawings.
[0078] Figure 1 and 2 is a diagram showing a method for producing a sulfur-carbon composite material according to Example 1.
[0079] Figure 3 3 is a graph showing the results of thermogravimetric analysis (TGA) of the sulfur-carbon composite material of Example 1.
[0080] Figure 4 : is a graph showing the results of X-ray diffraction (XRD) analysis of the sulfur-carbon composite materials of Example 1 and Comparative Example 1.
[0081] Figure 5It is a graph showing the results of Fourier transform infrared spectroscopy (FT-IR) analysis of the sulfur-carbon composite materials of Example 1 and Comparative Example 1.
[0082] Figure 6 The graph shows the results of transmission electron microscopy (TEM) analysis of the sulfur-carbon composite materials of Example 1 and Comparative Example 1.
[0083] Figure 7 3 is a diagram showing the results of scanning electron microscopy (SEM) analysis of the sulfur-carbon composite materials of Example 1 and Comparative Example 1.
[0084] Figures 8 to 10 is a graph showing discharge capacities evaluated by charging / discharging the lithium-sulfur batteries according to Example 1 and Comparative Example 1 at 25°C.
[0085] Fig.11 is a graph showing discharge capacities evaluated by charging / discharging the lithium-sulfur batteries according to Comparative Example 1 and Examples 2 to 4 at 25°C.
[0086] Fig.12 is a graph showing discharge capacities evaluated by charging / discharging the lithium-sulfur batteries according to Example 5 and Comparative Example 1 at 25°C.
[0087] Fig.13 is a Nyquist diagram showing the resistance of the lithium-sulfur batteries according to Example 1 and Comparative Example 1 before and after the battery test. DETAILED DESCRIPTION
[0088] Hereinafter, the present invention will be described in more detail.
[0089] It should be understood that the terms or words used in the specification and the appended claims should not be interpreted as limited to the general and dictionary meanings, but should be interpreted according to the meanings and concepts corresponding to the technical aspects of the present invention, based on the principle that the inventor appropriately defines the terms for the best interpretation.
[0090] Unless the context clearly indicates otherwise, when used in this specification, the terms “comprising”, “including” or “having” specify the presence of stated elements, but do not preclude the presence or addition of one or more other elements.
[0091] The present invention relates to a cross-linked polythiophene compound, a sulfur-carbon composite material comprising the cross-linked polythiophene compound, a lithium-sulfur battery comprising the sulfur-carbon composite material, a method for manufacturing the sulfur-carbon composite material, an electrochemical battery comprising the cross-linked polythiophene compound, and a method for manufacturing the same.
[0092] In the present invention, the electrochemical cell may include any type of battery in which an electrochemical reaction occurs. Specific examples of the electrochemical cell include any type of primary battery, secondary battery, fuel cell, solar cell, and capacitor such as a supercapacitor, etc. In particular, the electrochemical cell may be a secondary battery, and the secondary battery may be a lithium ion secondary battery. The lithium ion secondary battery may include, for example, a lithium metal battery, a lithium sulfur battery, an all-solid-state battery, a lithium polymer battery, etc., wherein a lithium sulfur battery is preferred.
[0093] Among secondary batteries, lithium-sulfur batteries have high discharge capacity and theoretical energy density, and because sulfur used as a positive electrode active material is abundant and inexpensive on Earth, the battery manufacturing cost required for lithium-sulfur batteries is low and environmentally friendly, so they are attracting attention as next-generation secondary batteries.
[0094] In the present invention, the positive electrode active material includes a carbon-sulfur composite material, and the carbon-sulfur composite material includes a porous carbon material. In lithium-sulfur batteries, since the positive electrode active material sulfur is not conductive, a carbon-sulfur composite material in which a conductive material such as a carbon material is combined with sulfur is generally used to improve conductivity.
[0095] According to one aspect of the present invention, there is provided a cross-linked polythiophene compound having a cross-linked structure and comprising a cationic functional group.
[0096] According to one embodiment of the present invention, the cationic functional group may include a variety of cationic functional groups to make the cross-linked polythiophene compound conductive. In one embodiment, the cationic functional group may include at least one of nitrogen cations, oxygen cations or sulfur cations. For example, the cationic functional group may include nitrogen cations. Specifically, the cationic functional group may be a quaternary ammonium functional group, and the cross-linked polythiophene compound may include a dialkylamine group with a quaternary ammonium functional group. In particular, when the cationic functional group is a quaternary ammonium, the adsorption of lithium polysulfide may be made easier than functional groups such as ethylene glycol that help lithium to move.
[0097] In addition, according to one embodiment of the present invention, since the cross-linked polythiophene compound has a cross-linked structure, rigidity can be improved. Generally, when the battery is charged and discharged, excessive volume expansion or swelling occurs, and the compound of the present invention can have high rigidity and make the material resist volume expansion or swelling.
[0098] According to one embodiment of the present invention, the cross-linked polythiophene compound may further include a counter ion of the cation included in the cationic functional group, and for example, the counter ion may be a halogen anion (e.g., F - , Cl - Br - ,I -In one embodiment of the present invention, the counter ion may be derived from the cross-linking agent used to cross-link the cross-linked polythiophene compound.
[0099] According to one embodiment of the present invention, the cross-linked polythiophene compound may be represented by Chemical Formula 1 as follows.
[0100] [Chemical formula 1]
[0101]
[0102] In the above chemical formula 1,
[0103] R 1 , R 3 , R 5 , R 7 and R 9 may each independently be a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms, and
[0104] R 2 and R 6 may each independently be a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 20 carbon atoms, or a -COO- group,
[0105] R 4 and R 8 It can be a divalent cation linking group,
[0106] A can be a halogen (F, Cl, Br, I, etc.), and
[0107] n and m may each independently be 1 to 1,000,000.
[0108] According to one embodiment of the present invention, the divalent cation linking group may be -NR 10 R 11 , R 10 and R 11 Each may independently be hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0109] According to one embodiment of the present invention, by adjusting R 1 , R 3 , R 5 , R 7 and R 9 The bond length of the cross-linked polythiophene compound can be used to adjust the polarity of the cross-linked polythiophene compound, thereby adjusting the crystallinity and thermal properties of the cross-linked polythiophene compound.
[0110] According to one embodiment of the present invention, the cross-linked polythiophene compound may be represented by Chemical Formula 2 as follows.
[0111] [Chemical formula 2]
[0112]
[0113] In the above Chemical Formula 2, n and m may each independently be 1 to 1,000,000.
[0114] According to another aspect of the present invention, there is provided a sulfur-carbon composite material, the sulfur-carbon composite material comprising:
[0115] Porous carbon materials;
[0116] A coating layer provided on at least one surface of the porous carbon material and comprising the cross-linked polythiophene compound; and
[0117] A sulfur compound present in at least a portion of the surface of the porous carbon material or the inside of the pores or the surface of the coating layer.
[0118] According to one embodiment of the present invention, the weight ratio of the porous carbon material to the cross-linked polythiophene compound may be 99:1 to 85:15 or 99:1 to 90:10.
[0119] The porous carbon material includes a plate-like carbon material. The specific surface area of the porous carbon material can be 1,000 m 2 / g or more, and the pore volume of the porous carbon material can be 4 cm 3 / g or above.
[0120] The porous carbon material may have a high specific surface area to increase the active sites of sulfur participating in the oxidation / reduction reaction. In addition, the porous carbon material may have a high pore volume to ensure high sulfur loading and sufficient ion diffusion paths.
[0121] The sulfur-carbon composite material includes a porous carbon material as a carrier for loading sulfur-containing compounds. Specifically, the sulfur-carbon composite material may include a plate-like porous carbon material as the porous carbon material. The plate-like porous carbon material may include, for example, graphene, graphene oxide, reduced graphene oxide (rGO) or a mixture thereof.
[0122] In one embodiment of the present invention, the plate-like porous carbon material may include only reduced graphene oxide.
[0123] Porous carbon materials can have 1,000 m 2Specifically, the upper limit of the Brunauer-Emmett-Teller (BET) specific surface area of the porous carbon material is not limited to a specific range, and may be, for example, 1,000 m 2 / g or more and 1,500 m 2 / g or less, 1,300 m 2 / g or less, 1,200 m 2 / g or less, 1,100 m 2 / g or less or 1,050 m 2 The sulfur-carbon composite material according to one embodiment of the present invention may include a plurality of micropores on its outer surface and / or inside and have a very high specific surface area.
[0124] The BET specific surface area can be measured by the BET method and indicates a value measured by a known method for measuring the BET specific surface area. For example, the BET specific surface area can be a value calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-max of BEL Japan.
[0125] Porous carbon materials can have a 4 cm 3 Specifically, the upper limit of the pore volume of the porous carbon material is not limited to a specific range, and may be, for example, 4 cm 3 / g or more and 15 cm 3 / g or less, 6 cm 3 / g or more and 10 cm 3 / g or less, 6 cm 3 / g or more and 8 cm 3 / g or less or 6.5 cm 3 / g or more and 7.5 cm 3 For example, the pore volume may be a measured value calculated by N2 isotherm analysis obtained based on liquid nitrogen adsorption.
[0126] As described above, the porous carbon material in the sulfur-carbon composite material according to one aspect of the present invention may include a plurality of micropores to support the sulfur-containing compound.
[0127] In one embodiment of the present invention, the porous carbon material may include a plurality of micropores on its outer surface and inside, and in this case, the micropores may include mesopores having a diameter of 1 nm or more and less than 50 nm and macropores having a diameter of 50 nm or more and 200 nm or less. In one embodiment of the present invention, the porous carbon material may have uniformly distributed mesopores and macropores.
[0128] The diameter of the micropores can be measured by methods known in the art for measuring the pore size of porous materials, and the measuring method is not limited to a specific type. For example, the average diameter of the micropores can be measured by scanning electron microscopy (SEM), field emission electron microscopy or laser diffraction. Measurement using laser diffraction can use, for example, a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000).
[0129] In another embodiment of the present invention, the average pore diameter (D50) of the porous carbon material may be, for example, 20 nm to 25 nm, but is not limited thereto. The average diameter (D50) refers to the particle diameter at 50% in the cumulative particle size distribution.
[0130] In the present invention, the sulfur compound is contained in at least a part of the inside and the outer surface of the pores of the porous carbon material having the above-mentioned characteristics.
[0131] The sulfur compound may include, but is not limited to, any type of sulfur compound that can be used as a positive electrode active material in a lithium-sulfur secondary battery. For example, the sulfur compound may include inorganic sulfur (S8), lithium polysulfide (Li2S n , 1≤n≤8), carbon-sulfur polymer (C2S x ) m , 2.5≤x≤50, 2≤m) or a mixture thereof, but not limited thereto.
[0132] The sulfur compound may be included in the sulfur-carbon composite material by physical adsorption on the porous carbon material or by a chemical bond such as a covalent bond, a van-deer-Waals bond, etc. between sulfur and carbon in the porous carbon material.
[0133] In one embodiment of the present invention, the porous carbon material and the sulfur compound may be included in the sulfur-carbon composite material in a weight ratio of, for example, 1:9 to 9:1, specifically 1:9 to 5:5, 1:9 to 4:6, 1:9 to 3:7, or 1:9 to 1.5:8.5. When the weight ratio of the porous carbon material to the sulfur compound in the sulfur-carbon composite material is within the above range, the kinetic activity of the sulfur-carbon composite material may be increased and the conductivity may be improved by the porous carbon material because the content of the sulfur compound is large, but the present invention is not limited thereto.
[0134] In another embodiment of the present invention, the amount of the sulfur compound in the sulfur-carbon composite material can be, for example, 10% by weight or more, specifically 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, or 85% by weight or more, based on the total weight of the sulfur-carbon composite material. In addition, the amount of the sulfur compound in the sulfur-carbon composite material can be 50% by weight to 90% by weight within the above range, specifically 60% by weight to 90% by weight, 70% by weight to 90% by weight, or 85% by weight to 90% by weight, based on the total weight of the sulfur-carbon composite material. When the amount of the sulfur compound in the sulfur-carbon composite material is within the above range, because the content of the sulfur compound is large, the kinetic activity of the sulfur-carbon composite material can be increased and the conductivity can be improved by the porous carbon material, but the present invention is not limited thereto.
[0135] In one embodiment of the present invention, the average particle size (D50) of the sulfur-carbon composite material can be, for example, 0.5 μm to 200 μm, 1 μm to 150 μm, or 10 μm to 150 μm. The particle size of the sulfur-carbon composite material can be measured by SEM, field emission electron microscopy or laser diffraction. Measurement using laser diffraction can use, for example, a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000). The average particle size (D50) refers to the particle size at 50% in the cumulative particle size distribution.
[0136] In one embodiment of the present invention, the Raman peak intensity ratio (I G / I D Ratio) can be less than 1. For example, when I G / I D When the ratio is equal to or less than 1, it is possible to prevent the reduction in efficiency of the conversion reaction of the combination with the sulfur-containing compound or lithium polysulfide due to too high surface crystallinity of the sulfur-carbon composite material.
[0137] The Raman peak intensity ratio can be obtained by the I obtained from the spectrum of the carbon composite material obtained by Raman spectroscopy. G and I D In the obtained spectrum, I G The peak representing the crystalline part (G peak, 1,573 / cm), and I D Indicates the peak of the amorphous part (D peak, 1,309 / cm). Therefore, in this case, I G / I D The smaller the ratio, the lower the crystallinity.
[0138] In one embodiment of the present invention, the sulfur-carbon composite material may be formed by mixing a porous carbon material with a sulfur compound and performing a heat treatment, but the manufacturing method of the present invention is not limited thereto.
[0139] Because the sulfur-carbon composite material of the present invention as described above includes a plate-like carbon material having a high specific surface area and a high pore volume, the sulfur loading amount can be enhanced and multiple active sites for sulfur oxidation / reduction reactions can be provided, thereby improving battery efficiency and energy density when used for the positive electrode of a lithium-sulfur battery, but the mechanism of the present invention is not limited thereto.
[0140] In the sulfur-carbon composite material of the present invention, the coating layer may contain the cross-linked polythiophene compound. For example, the weight ratio of the porous carbon material to the cross-linked polythiophene compound may be 99:1 to 85:15 or 99:1 to 90:10. In addition, the weight ratio of the porous carbon material with the coating layer to the sulfur compound may be 3:7 to 4:6.
[0141] According to another aspect of the present invention, there is provided a method for manufacturing a sulfur-carbon composite material, the method comprising the following steps:
[0142] introducing a polythiophene compound into a dispersion of a porous carbon material to coat the polythiophene compound on at least one surface of the porous carbon material;
[0143] cross-linking the polythiophene compound coated on the porous carbon material to form a cross-linked polythiophene compound; and
[0144] The sulfur compound is loaded into the porous carbon material coated with the cross-linked polythiophene compound.
[0145] According to another aspect of the present invention, there is provided a method for manufacturing a sulfur-carbon composite material, the method comprising the following steps:
[0146] cross-linking the polythiophene compound to form a cross-linked polythiophene compound;
[0147] loading a sulfur compound into a porous carbon material; and
[0148] The cross-linked polythiophene compound is coated on at least one surface of the porous carbon material supported with the sulfur compound.
[0149] The sulfur-carbon composite material according to the present invention can be manufactured by the above two manufacturing methods. For example, like the previous manufacturing method, the cross-linked polythiophene compound can be formed by in-situ polymerization of the polythiophene compound in the porous carbon material, and the sulfur compound can be loaded into the porous carbon material coated with the cross-linked polythiophene compound.
[0150] Alternatively, like the latter production method, the cross-linked polythiophene compound may be formed by ex-situ polymerization of the polythiophene compound, and the cross-linked polythiophene compound may be coated on the porous carbon material supported with the sulfur compound.
[0151] According to one embodiment of the present invention, the cross-linked polythiophene compound may be formed by adding a cross-linking agent to a porous carbon material coated with the polythiophene compound and performing a heat treatment.
[0152] According to one embodiment of the present invention, the polythiophene compound may be represented by Chemical Formula 3 as follows.
[0153] [Chemical formula 3]
[0154]
[0155] In the above chemical formula 3,
[0156] R 1 and R 3 may each independently be a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms,
[0157] R 2 It may be a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 20 carbon atoms, or a -COO- group,
[0158] R 12 Can be -NR 10 R 11 , R 10 and R 11 may each independently be hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and
[0159] n can be from 1 to 1,000,000.
[0160] According to one embodiment of the present invention, the method for preparing a polythiophene compound may include the following steps:
[0161] preparing a thiophene monomer having a thiophene group and a cationic functional group;
[0162] introducing a thiophene monomer into a dispersion of a porous carbon material; and
[0163] The thiophene monomers are polymerized.
[0164] The steps of preparing the thiophene monomer may include the following steps:
[0165] Preparation of thiophene compounds having anionic functional groups;
[0166] reacting a thiophene compound with a chloride; and
[0167] The thiophene compound subjected to the reaction with the chloride is reacted with a cationic alcohol compound to produce a thiophene monomer.
[0168] According to one embodiment of the present invention, the thiophene compound may be represented by Chemical Formula 4 as follows.
[0169] [Chemical formula 4]
[0170]
[0171] In the above chemical formula 4, R 1 The anionic functional group may be an anionic functional group, and for example, the anionic functional group may include at least one of -COOH, -SO3H, -PhOH, or -ArSO3H.
[0172] According to one embodiment of the present invention, the chloride may be various chlorides including -Cl, and when R 1 When is -COOH and the chloride is SOCl2, the thiophene compound after undergoing the reaction with the chloride may have the following Chemical Formula 5.
[0173] [Chemical formula 5]
[0174]
[0175] According to one embodiment of the present invention, the thiophene monomer may be manufactured by a reaction between a thiophene compound (eg, a compound represented by Chemical Formula 5) subjected to a reaction with a chloride and an alcohol compound having a cationic functional group.
[0176] For example, the alcohol compound may be 2-dimethylaminoethanol, and the thiophene monomer may be represented by Chemical Formula 6 below.
[0177] [Chemical formula 6]
[0178]
[0179] Since the cross-linked polythiophene compound having a cationic functional group is coated on the porous carbon material, the lithium polysulfide leaked from the positive electrode of the lithium-sulfur battery can be prevented from migrating to the negative electrode by the cationic functional group. Therefore, sulfur particles can be prevented from accumulating on the lithium metal surface of the negative electrode, thereby maintaining the charge and discharge capacity of the lithium-sulfur battery and improving the battery life.
[0180] A method of manufacturing a sulfur-carbon composite material according to one embodiment of the present invention may be as follows.
[0181] First, as described above, a thiophene compound having an anionic functional group (eg, -COOH) is prepared and reacted with a chloride (eg, SOCl2) in a solution at a high temperature (eg, 80°C to 100°C).
[0182] Here, the solvent is not limited to a specific type and may include any type of solvent capable of dissolving or dispersing the compound. The solvent may be, for example, a chlorine-containing solvent such as chloroform, dichloromethane, 1,2-dichloroethane, 1,1,2-trichloroethane, chlorobenzene, ortho-dichlorobenzene; an ether solvent such as tetrahydrofuran, dichloroethane, ortho-dichlorobenzene; Alkanes; aromatic hydrocarbon solvents such as toluene, xylene, trimethylolene, mesitylene; aliphatic hydrocarbon solvents such as cyclohexane, methylcyclohexane, n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone; ester solvents such as ethyl acetate, butyl acetate, ethyl cellosolve acetate; polyols such as ethylene glycol, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, dimethoxyethane, propylene glycol, diethoxymethane, triethylene glycol monoethyl ether, glycerol, 1,2-hexanedialdehyde and its derivatives; alcohol solvents such as methanol, ethanol, propanol, isopropanol, cyclohexanol; sulfoxide solvents such as dimethyl sulfoxide; amide solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide; benzoate solvents such as butyl benzoate, methyl 2-methoxybenzoate; tetralin; 3-phenoxytoluene.
[0183] The thiophene monomer can be produced by reacting a thiophene compound after undergoing a reaction with a chloride with, for example, 2-dimethylaminoethanol and triethylamine (TEA) in a solvent. Subsequently, the thiophene monomer can be dissolved in a solvent and then introduced into a solution in which a porous carbon material (such as Ketjen black (KB)) and a chloride (such as FeCl3) are dispersed to form a polythiophene compound by in-situ polymerization of the thiophene monomer on the surface of the porous carbon material.
[0184] A crosslinking agent may be added to a dispersion of a porous carbon material coated with a polythiophene compound and heat treated to form a crosslinked polythiophene compound. For example, the crosslinking agent may be a dihalogenated alkane compound (e.g., 1,4-dibromobutane, 1,4-dichlorobutane, diiodobutane, dichlorobutane, and a mixture thereof), and Figure 1 As shown in , it can be diiodobutane.
[0185] Hereinafter, specific embodiments will be described in detail to help better understand the present invention. However, examples according to the present invention can be changed in many other forms, and the scope of the present invention should not be interpreted as being limited to the following examples. Embodiments of the present invention are provided to fully illustrate the present invention to those of ordinary skill in the art.
[0186] Example 1
[0187] Preparation of sulfur-carbon composite materials and positive electrodes
[0188] A thiophene compound having -COOH as an anion functional group was prepared and reacted with SOCl2 as a chloride in a solvent at 90° C. Here, benzene was used as the solvent.
[0189] The thiophene compound after the reaction with the chloride was dissolved in a dichloromethane solvent, and 2-dimethylaminoethanol and triethylamine (TEA) were added to produce a thiophene monomer. The thiophene monomer was dissolved in a chloroform solvent and introduced into a chloroform solvent in which Ketjen black (KB) as a porous carbon material and FeCl3 as a chloride were dispersed, followed by ultrasonic treatment for 3 hours. Subsequently, a polythiophene compound was formed by in-situ polymerization of the thiophene monomer on the surface of Ketjen black (see Figure 1 ).
[0190] Diiodobutane as a crosslinking agent is added to the dispersion of the porous carbon material coated with the polythiophene compound, and the dialkylamine group as the cationic functional group of the polythiophene compound is activated by the crosslinking agent to crosslink the polythiophene compound to obtain a crosslinked polythiophene compound.
[0191] For the positive electrode active material, a sulfur-carbon composite material (CPTqD10-KB-S) was used, which was prepared by loading a sulfur compound into Ketjen black (CPTqD10-KB) coated with a cross-linked polythiophene compound. The weight ratio of Ketjen black to the cross-linked polythiophene compound was 90:10. The sulfur-carbon composite material, polyacrylic acid (PAA) (weight average molecular weight of 450,000) as a binder, and Super P as a carbon conductive material were mixed in a weight ratio of 85:10:5, and 0.5% of polyvinyl alcohol (PVA) (weight average molecular weight of 9,500) as a dispersant was added to prepare a positive electrode slurry with a solid concentration of 18% by weight, and the positive electrode slurry was uniformly coated on an aluminum foil to a thickness of 400 μm and dried at 50°C to manufacture a positive electrode (see Figure 2 ).
[0192] Preparation of lithium-sulfur batteries
[0193] For the separator, a polyethylene porous film (Celgard separator) was used, and for the negative electrode, lithium metal was used. 1.0 M LiNO3 was added to a mixed solvent of 1,3-dioxolane (DOL) and 1,2-dimethyl ether in a volume ratio (volume / volume) of 50:50 to prepare an electrolyte for a lithium-sulfur secondary battery.
[0194] The positive electrode and negative electrode prepared as described above were placed with a separator interposed therebetween to prepare an electrode assembly, the electrode assembly was put into a coin-shaped battery case, and the prepared electrolyte was injected to prepare a coin cell type lithium sulfur battery.
[0195] Example 2
[0196] Preparation of sulfur-carbon composite materials and positive electrodes
[0197] The sulfur compound is loaded into Ketjen black, and then the cross-linked polythiophene compound is coated on the Ketjen black loaded with the sulfur compound. That is, the cross-linked polythiophene compound is prepared and coated by ex-situ polymerization of the polythiophene compound, and the weight ratio of Ketjen black to the cross-linked polythiophene compound is 99:1.
[0198] Preparation of lithium-sulfur batteries
[0199] A lithium-sulfur battery was prepared by the same method as in Example 1, except that the positive electrode prepared in Example 2 was used.
[0200] Example 3
[0201] Preparation of sulfur-carbon composite materials and positive electrodes
[0202] A sulfur-carbon composite material and a positive electrode were prepared by the same method as in Example 2, except that the weight ratio of Ketjen black to the cross-linked polythiophene compound was 93:7.
[0203] Preparation of lithium-sulfur batteries
[0204] A lithium-sulfur battery was prepared by the same method as in Example 1, except that the positive electrode prepared in Example 3 was used.
[0205] Example 4
[0206] Preparation of sulfur-carbon composite materials and positive electrodes
[0207] A sulfur-carbon composite material and a positive electrode were prepared by the same method as in Example 2, except that the weight ratio of Ketjen black to the cross-linked polythiophene compound was 95:5.
[0208] Preparation of lithium-sulfur batteries
[0209] A lithium-sulfur battery was prepared by the same method as in Example 1, except that the positive electrode prepared in Example 4 was used.
[0210] Example 5
[0211] Preparation of sulfur-carbon composite materials and positive electrodes
[0212] A sulfur-carbon composite material and a positive electrode were prepared by the same method as in Example 1, except that the weight ratio of Ketjen black to the cross-linked polythiophene compound was 95:5.
[0213] Preparation of lithium-sulfur batteries
[0214] A lithium-sulfur battery was prepared by the same method as in Example 1, except that the positive electrode prepared in Example 5 was used.
[0215] Comparative Example 1
[0216] Preparation of sulfur-carbon composite materials and positive electrodes
[0217] A sulfur-carbon composite material and a positive electrode were prepared by the same method as in Example 1, except that a sulfur-carbon composite material in which Ketjen black and a sulfur compound were mixed at a weight ratio of 3:7 was used as a positive electrode active material.
[0218] Preparation of lithium-sulfur batteries
[0219] A lithium-sulfur battery was prepared by the same method as in Example 1, except that the positive electrode prepared in Comparative Example 1 was used.
[0220] Analyze the results
[0221] Thermogravimetric analysis (TGA) results
[0222] Figure 3 Shown are TGA analysis results of the sulfur-carbon composite material of Example 1. According to the TGA analysis results, in the sulfur-carbon composite material including Ketjen black coated with a cross-linked polythiophene compound and a sulfur compound, the loading amount of the sulfur compound was 61 wt % when measured.
[0223] X-ray diffraction (XRD) analysis results
[0224] Figure 4 The XRD analysis results of the sulfur-carbon composite materials of Example 1 and Comparative Example 1 are shown. According to the XRD analysis results, the peak of the cross-linked polythiophene compound of Example 1 was observed at 2θ=25±5°.
[0225] Fourier transform infrared spectroscopy (FT-IR) analysis results
[0226] Figure 5 The FT-IR analysis results of the sulfur-carbon composite materials of Example 1 and Comparative Example 1 are shown. According to the FT-IR analysis results, characteristic peaks of the cross-linked polythiophene compound of Example 1 and the quaternary ammonium functional group contained therein are present.
[0227] Transmission electron microscopy (TEM) analysis results
[0228] Figure 6 The TEM analysis results of the sulfur-carbon composite materials of Example 1 and Comparative Example 1 are shown. The TEM analysis results confirmed that the cross-linked polythiophene compound was coated on the Ketjen Black of Example 1.
[0229] Scanning electron microscopy (SEM) analysis results (surface observation)
[0230] Figure 7 The SEM analysis results of the sulfur-carbon composite materials of Example 1 and Comparative Example 1 are shown. The SEM analysis results confirmed that the cross-linked polythiophene compound was coated on the Ketjen Black of Example 1.
[0231] Charge and discharge evaluation
[0232] Figure 8 : is a graph showing the discharge capacity evaluated by charging and discharging the lithium-sulfur batteries according to Example 1 and Comparative Example 1 at 25° C. under the following conditions.
[0233] Tester: WBSC3000 Battery Cycler (WonAtech)
[0234] Current density: 0.2 C rate
[0235] refer to Figure 8 , when measured, the lithium-sulfur battery according to Example 1 had a higher discharge capacity in 1 cycle to 120 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0236] Fig. 9 : is a graph showing the discharge capacity evaluated by charging and discharging the lithium-sulfur batteries according to Example 1 and Comparative Example 1 at 25° C. under the following conditions.
[0237] Tester: WBSC3000 Battery Cycler (WonAtech)
[0238] Current density: 0.5 C rate
[0239] refer to Fig. 9 , when measured, the lithium-sulfur battery according to Example 1 had a higher discharge capacity in 1 cycle to 200 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0240] Fig.10 : is a graph showing the discharge capacity evaluated by charging and discharging the lithium-sulfur batteries according to Example 1 and Comparative Example 1 at 25° C. under the following conditions.
[0241] Tester: WBSC3000 Battery Cycler (WonAtech)
[0242] Current density: 1 C rate
[0243] refer to Fig.10 , when measured, the lithium-sulfur battery according to Example 1 had a higher discharge capacity in 40 cycles to 160 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0244] Fig.11is a graph showing the discharge capacity evaluated by charging and discharging the lithium-sulfur batteries according to Comparative Example 1 and Examples 2 to 4 at 25° C. under the following conditions.
[0245] Tester: WBSC3000 Battery Cycler (WonAtech)
[0246] Current density: 0.2 C rate
[0247] refer to Fig.11 , when measured, the lithium-sulfur batteries according to Examples 2 to 4 had higher discharge capacities in 1 cycle to 70 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0248] Fig.12 : is a graph showing the discharge capacity evaluated by charging and discharging the lithium-sulfur batteries according to Example 5 and Comparative Example 1 at 25° C. under the following conditions.
[0249] Tester: WBSC3000 Battery Cycler (WonAtech)
[0250] Current density: 0.2 C rate
[0251] refer to Fig.12 , when measured, the lithium-sulfur battery according to Example 5 had a higher discharge capacity in 1 cycle to 120 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0252] Fig.13 The Nyquist plots of the resistance of the lithium-sulfur batteries of Example 1 and Comparative Example 1 before and after 200 cycles of battery testing at a rate of 0.5 C are shown in FIG. Fig.13 , when measured, the lithium-sulfur battery according to Example 1 had an improved resistance value before and after the battery test compared to the lithium-sulfur battery according to Comparative Example 1.
Claims
1. A cross-linked polythiophene compound having a cross-linked structure and containing a cationic functional group. 2 . The cross-linked polythiophene compound according to claim 1 , wherein the cationic functional group comprises at least one of a nitrogen cation, an oxygen cation or a sulfur cation. The cross-linked polythiophene compound according to claim 2 , wherein the cationic functional group is a quaternary ammonium functional group. The cross-linked polythiophene compound according to claim 3 , wherein the cross-linked polythiophene compound comprises a dialkylamine group having the quaternary ammonium functional group. 5 . The cross-linked polythiophene compound according to claim 1 , further comprising a halogen anion as a counter ion of the cation contained in the cationic functional group.
6. The cross-linked polythiophene compound according to claim 1, wherein the cross-linked polythiophene compound is represented by the following Chemical Formula 1: [Chemical formula 1] Wherein in Chemical Formula 1, R 1 , R 3 , R 5 , R 7 and R 9 are each independently a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms, R 2 and R 6 are each independently a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 20 carbon atoms, or a -COO- group, R 4 and R 8 is a divalent cation linking group, A is F, Cl, Br or I, and n and m are each independently 1 to 1,000,000.
7. The cross-linked polythiophene compound according to claim 6, wherein the divalent cation linking group is -NR 10 R 11 , and R 10 and R 11 Each is independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
8. The cross-linked polythiophene compound according to claim 6, wherein the cross-linked polythiophene compound is represented by the following Chemical Formula 2: [Chemical formula 2] In Chemical Formula 2, n and m are each independently 1 to 1,000,000.
9. A sulfur-carbon composite material, comprising: Porous carbon materials; a coating layer provided on at least one surface of the porous carbon material and comprising the cross-linked polythiophene compound according to any one of claims 1 to 8; and A sulfur compound is present in at least a portion of the surface of the porous carbon material or the inside of the pores of the porous carbon material or the surface of the coating layer. 10 . The sulfur-carbon composite material according to claim 9 , wherein a weight ratio of the porous carbon material to the cross-linked polythiophene compound is 99:1 to 85:
15. 11 . The sulfur-carbon composite material according to claim 9 , wherein a weight ratio of the porous carbon material having a coating layer to the sulfur compound is 3:7 to 4:
6.
12. A lithium-sulfur battery, comprising: a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode, The positive electrode comprises the sulfur-carbon composite material according to claim 9.
13. A method for manufacturing the sulfur-carbon composite material according to claim 9, the method comprising the following steps: introducing a polythiophene compound into a dispersion of a porous carbon material to coat the polythiophene compound on at least one surface of the porous carbon material; cross-linking the polythiophene compound coated on the porous carbon material to form a cross-linked polythiophene compound; and A sulfur compound is loaded into the porous carbon material coated with the cross-linked polythiophene compound. 14 . The method for producing a sulfur-carbon composite material according to claim 13 , wherein the cross-linked polythiophene compound is formed by adding a cross-linking agent to the porous carbon material coated with the polythiophene compound and performing a heat treatment.
15. The method for producing a sulfur-carbon composite material according to claim 14, wherein the cross-linking agent comprises a dihalogenated alkane compound.
16. The method for producing a sulfur-carbon composite material according to claim 13, wherein the polythiophene compound is represented by the following Chemical Formula 3: [Chemical formula 3] Wherein in chemical formula 3, R 1 and R 3 are each independently a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms, R 2 is a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 20 carbon atoms, or a -COO- group, R 12 For-NR 10 R 11 , R 10 and R 11 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and n is 1 to 1,000,000.
17. The method for manufacturing a sulfur-carbon composite material according to claim 16, wherein the method for preparing the polythiophene compound comprises the following steps: manufacturing a thiophene monomer having a thiophene group and a cationic functional group; introducing the thiophene monomer into a dispersion of the porous carbon material; and The thiophene monomers are polymerized. 18 . The method for producing a sulfur-carbon composite material according to claim 17 , wherein the thiophene monomer is in-situ polymerized on the surface of the porous carbon material.
19. The method for producing a sulfur-carbon composite material according to claim 17, wherein the production of the thiophene monomer comprises the following steps: preparing a thiophene compound having an anionic functional group; reacting the thiophene compound with a chloride; and The thiophene compound subjected to the reaction with the chloride is reacted with an alcohol compound having the cationic functional group to produce the thiophene monomer.
20. A method for manufacturing the sulfur-carbon composite material according to claim 9, the method comprising the following steps: cross-linking the polythiophene compound to form a cross-linked polythiophene compound; loading a sulfur compound into a porous carbon material; and The cross-linked polythiophene compound is coated on at least one surface of the porous carbon material loaded with the sulfur compound.
Citation Information
Patent Citations
Generating synthetic test cases for fuzz testing
KR1020220118937A
